PENERAPAN PUPUK HAYATI JAMUR MIKORIZA DAN BAKTERI FOTOSINTAT PADA TANAMAN SAYURAN DI KELOMPOK TANI DAMANG SAIYO KABUPATEN LIMA PULUH KOTA - Yefriwati, Yefriwati; Rizki, Rizki; Achmad, Benny Satria; Rasdanelwati, Rasdanelwati; Darmansyah, Darmansyah; Alfina, Rina; Darlis, Olivia; Chan, Sari Rukmana Okta Sagita; Chairunnisak, Chairunnisak (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Damang Saiyo farmer group operates in food crop and vegetable farming. Community service activities in the Damang Saiyo farmer group are conducted using training and application of organic fertilizer from mycorrhizal fungi and photosynthetic bacteria to overcome farmers' problems regarding fertilizer scarcity so that fertilizer is available for plants. One of the technologies applied is mycorrhizal fungi and photosynthetic bacteria. (PSB). Mycorrhizal fungi are a type of biological fertilizer with a mutualistic symbiotic relationship with plant roots, which is beneficial for plants so that plant growth is good. At the same time, photosynthetic bacteria (PSB) are autotrophic bacteria that can photosynthesize and have pigments called bacteriophages a or b. can produce red, green, and purple pigments to capture solar energy as fuel for photosynthesis. The objectives of this community service activity are as follows: (1). Providing information on how to apply Organic fertilizers/biological mycorrhizal fungi and photosynthetic bacteria to vegetable plants, (2). Increase farmers' insight into using biofertilizers for mycorrhizal fungi and photosynthetic bacteria to increase farmers' income. This community service activity occurred at Jorong Balai Kenagarian Batu Balang, Harau District, from June to October 2023. The results of the actions show that the community has been able to make organic/biological fertilizer for mycorrhizal fungi and photosynthetic bacteria and has been able to apply it generously to vegetable plants.